A REVIEW ON APPROACHES USED TO OVERCOME PROBLEMS ASSOCIATED WITH CONVENTIONAL DOSAGE FORMS OF H2 ANTAGONIST - Mahalaxmi Rathnanand (Journal of Global Pharma Technology, 2018)
Gastro intestinal disease conditions includes acid reflux, heartburn, gastroesophageal reflux disease, dyspepsia, nausea and vomiting, peptic ulcer, abdominal pain, belching, swollen mucosal membrane with gastric fluids, the accumulation of gas in the alimentary canal, biliary tract and gallbladder infection. All these disorders are results of distinctive causes. Overlapping mechanism results in excessive acid secretion and diminished mucous defence. H2 antagonists generally most widely used in treatment of above conditions. Proton pump inhibitors shows therapeutic advances due to inhibition of most potent acid secretion. Neuronal stimulation and hormonal stimulation of receptor on basolateral and parietal membrane is modified by gastric HCl secretion. Cimetidine, ranitidine, famotidine, and nizatidine have been used to treat these conditions which act on H2 receptor. They are structural analogues of H2 receptor that causes decrease tonic activation rate of the receptor. H2 antagonists have disadvantages like handling, bitterness, moisture absorption, gastric emptying. This review mainly focuses on methods to improve problems related to H2 antagonists.